HUBUNGAN PENGETAHUAN DENGAN MOTIVASI SADARI BERBASIS TEORI MOTIVASI PROTEKSI PADA REMAJA PUTRI : The Relationship Between Knowledge and Breast Self-Examination Motivation Based on the theory of Protection Motivation in Adolescent girls - Nadhaafa Nur Karliena Karlie (Politeknik Kesehatan Kemenkes Bandung, 2025)
Breast cancer is the main cause of global cancer incidence of all cancer cases. Breast cancer is one of the five leading causes of death worldwide. Many breast tumors are found at a young age, even teenagers as young as 14 years old suffer from tumors in the breast which can potentially become cancer if not detected early. Efforts to detect breast cancer early can be done with BSE, which is a screening program to identify breast cancer when they are small, before the cancer has a chance to spread. This research aims to determine the relationship between BSE knowledge and motivation among teenagers at SMAN 1 Ciparay. This research uses a analytical design with a cross-sectional approach. This research allocated 170 class X female students at SMAN 1 Ciparay. Sampling technique using Stratified Random Sampling Technique. The research results of knowledge in the good category were 74.1% and motivation in the high category was 54.1%. The relationship between knowledge and motivation is that respondents who have less knowledge and low motivation are 63.6% more than respondents who have good knowledge and high motivation are 57.1%. The chi square test of knowledge with motivation obtained p value=0.018 (<0.05). Based on the results, it can be said that there is a relationship between knowledge and motivation in doing BSE.Conclusion The better the level of knowledge, the better the motivation for BSE (Self Breast Examination) as an Early Detection of Breast Cancer in Young Women. Key words: Breast cancer, Breast Self-Examination, Knowledge, Motivation, Female adolescents, Senior High School